Population Ageing In New Zealand: Implications for Living Standards and the Optimal Rate of Saving - Ross Guest; John Bryant; Grant Scobie (New Zealand Government, The Treasury, 2003)
Over the next 50 years, New Zealand's population will age substantially. There has been wide debate about whether New Zealand should prepare for population ageing by increasing national savings. The debate had not, however, involved explicit consideration of possible time paths for savings, consumption, debt, and other relevant macroeconomic variables; nor have explicit principles been offered for determining which of these time paths are to be preferred. This paper addresses the question of choosing time paths through the use of a Ramsey-Solow model of optimal saving, adapted for investigating problems of population ageing. The results suggest that population ageing alone would not justify increases in national savings rates beyond those envisaged by current policy. The cost of ageing in terms of reduced real consumption is not large enough to justify large additional savings beyond those currently predicted, and the concomitant reduction in current consumption. The findings concerning national savings and living standards are robust to a variety of specifications of demographic conditions, interest rates, and productivity growth.
Keywords: D9; E21; J11; 330; consumption; saving; inter-temporal paths; Ramsey model; population ageing; New Zealand